2006
DOI: 10.1158/0008-5472.can-05-4103
|View full text |Cite
|
Sign up to set email alerts
|

The p53 Pathway Promotes Efficient Mitochondrial DNA Base Excision Repair in Colorectal Cancer Cells

Abstract: The tumor suppressor p53 plays a central role in the DNA damage response. p53 enhances base excision repair (BER), in part, through direct interaction with the repair complex. Mitochondrial DNA (mtDNA) is repaired by a mtBER pathway. Many colorectal cancers harbor mtDNA mutations that are associated with poor prognosis. In addition to modulating the apoptotic response, mitochondria-localized p53 also stimulates mtBER. However, the mechanisms by which p53 enhances colorectal cancer mtBER after stress remain unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 50 publications
(137 reference statements)
3
52
0
5
Order By: Relevance
“…29 Furthermore, p53 enhances BER through direct interaction with the repair complex in an inner mitochondrial membrane subfraction. 8 The fact that p53 localizes to the mitochondria and interacts with mtDNA and pol g, taken together with our observations that the presence of p53 decreases the amount of incorporation of wrong nucleotide in H1299mit, suggests that p53 may be the fidelity-enhancing component of DNA replication machinery in mitochondria.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…29 Furthermore, p53 enhances BER through direct interaction with the repair complex in an inner mitochondrial membrane subfraction. 8 The fact that p53 localizes to the mitochondria and interacts with mtDNA and pol g, taken together with our observations that the presence of p53 decreases the amount of incorporation of wrong nucleotide in H1299mit, suggests that p53 may be the fidelity-enhancing component of DNA replication machinery in mitochondria.…”
Section: Discussionmentioning
confidence: 57%
“…[3][4][5][6] p53 was detected within the inner mitochondrial compartment, where mtDNA and mtBER components localize. 7,8,28 It was of interest to evaluate the incorporation and excision of the wrong nucleotide by mitochondrial extracts derived from isogenic HCT116 cells. p53 was detected in the mitochondrial fraction of HCT116 (p53 þ / þ ) cells (p53 þ / þ )mit), but not of HCT116 (p53À/À) cells (p53À/À)mit) with Do-1 anti-human p53 mAb (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The link of altered mtDNA, to both TP53 wild-type status and probably downregulated Bcl-2 protein expression in CRC, could point to an intact intrinsic apoptotic pathway, either despite of the types of mtDNA alterations found here or caused by these via a currently unknown mechanism. Preliminary results of basic research demonstrated that mutant mtDNA promotes apoptotic resistance 45,46 and that TP53 enhances base excision repair, 47 thus suggesting a link between wild-type TP53 and intact mtDNA genome. According to our data, the role of mtMSI in the apoptotic pathway could be different from the role of mtDNA mutations.…”
Section: Discussionmentioning
confidence: 99%
“…This interaction could account for a higher mtDNA copy number in p53 +/+ vs. p53 −/− cells. [48][49][50][51][52] We and others have previously characterized that endogenous p53 can be located at mitochondria in the absence of exogenous stress, further supporting that p53 has a role in the normal physiology of this organelle. [53][54][55] In the present study, our aim was to better characterize the intramitochondrial localization of p53 and to identify new partners and functions of p53 in mitochondria in the absence of induced stress.…”
Section: Introductionmentioning
confidence: 61%